Work Environment Organizational Culture And Motivation Driving Microfinance Employee Satisfaction: Lingkungan Kerja Budaya Organisasi Dan Motivasi Mendorong Kepuasan Karyawan Keuangan Mikro - Nabila Ikfina Dwi Qonita; Putu Lidia Marini; Luh Gede Putri Kusuma Pekerti (Indonesian Journal of Law and Economics Review, 2026)
General Background Human resources represent fundamental assets determining corporate competitiveness and long-term sustainability. Specific Background Rural banking institutions face unique personnel challenges, particularly regarding strict target achievements and repetitive routines that decrease employee satisfaction. Knowledge Gap Previous literature presents inconsistent findings regarding how workplace conditions and institutional norms dictate personnel fulfillment, leaving a void within the high-pressure microfinance sector. Aims This research analyzes how the work environment, organizational culture, and motivation collectively and individually dictate employee satisfaction at PT. BPR Nusamba Kubutambahan Negara Branch. Results Utilizing saturated sampling involving 30 respondents and multiple linear regression analysis, the findings demonstrate that work environment, organizational culture, and motivation concurrently and partially yield a positive and significant role in dictating employee satisfaction. Novelty This study distinctly combines these three simultaneous predictors specifically within a microfinance institution characterized by dynamic financial service pressures and continuous client interactions. Implications Bank management must prioritize cultivating comfortable physical workspaces, reinforcing positive corporate norms, and providing continuous motivation to maintain workforce loyalty and long-term operational success. Highlights Positive corporate norms significantly elevate personnel fulfillment within rural banking institutions. Comfortable physical surroundings directly dictate staff loyalty and operational continuity. Continuous personal incentives concurrently optimize workforce performance alongside institutional values. Keywords Work Environment; Organizational Culture; Employee Motivation; Job Satisfaction; Microfinance Institution